A Low‐Cost Tebuconazole‐Based Screening Test for Azole‐Resistant Aspergillus fumigatus. Issue 1 (28th August 2020) - Brackin, Amelie P.; Shelton, Jennifer M. G.; Abdolrasouli, Alireza; Fisher, Matthew C.; Sewell, Thomas R.
Abstract: The global emergence of azole resistance in Aspergillus fumigatus is resulting in health and food security concerns. Rapid diagnostics and environmental surveillance methods are key to understanding the distribution and prevalence of azole resistance. However, such methods are often associated with high costs and are not always applicable to laboratories based in the least‐developed countries. Here, we present and validate a low‐cost screening protocol that can be used to differentiate between azole‐susceptible "wild‐type" and azole‐resistant A. fumigatus isolates. © 2020 The Authors. Basic Protocol 1 : Preparation of Tebucheck multi‐well plates Basic Protocol 2 : Inoculation of Tebucheck multi‐well plates